Chemical Composition and Biological Activities of the Essential Oils of Chrysophyllum albidum G. Don (African Star Apple) - Daniel Nartey; Joseph Nana Gyesi; Lawrence Sheringham Borquaye (Biochemistry Research International)
The volatile compounds of the fruit and leaf essential oils of the African star fruit, Chrysophyllum albidum G. Don, were characterized by gas chromatography-mass spectrometry in this study. The antimicrobial, antibiofilm, and antioxidant activities of the essential oils were also investigated. Thirty-five and thirty-four compounds, representing 97.84% and 97.87%, were identified in the leaf and fruit essential oils, respectively. The antimicrobial activity of the oils was evaluated in vitro against eight pathogens using the broth microdilution method. The fruit essential oil exhibited broad-spectrum antimicrobial activity in the antimicrobial susceptibility test, with minimum inhibitory concentrations (MICs) ranging from 0.195 to 6.250 mg/mL, while the leaf essential oils showed antimicrobial activity with MICs in the range of 6.875–13.750 mg/mL. The antibiofilm activity was assessed via the crystal violet staining assay, with Pseudomonas aeruginosa as the model organism. The concentrations of the leaf and fruit essential oil required for half-maximal inhibition of biofilm formation (BIC50) were 6.97 ± 0.56 and 4.78 ± 0.21 mg/mL, respectively. In evaluating antioxidant activity, the total antioxidant capacity obtained from the phosphomolybdenum assay was 104.8 ± 2.4 and 101.6 ± 0.8 μg/g AAE for leaf and fruit essential oils, respectively. The IC50 values obtained from the hydrogen peroxide scavenging, 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging, and inhibition of lipid peroxidation assays were 301.8 ± 0.7 and 669.2 ± 2.1 μg/mL, 1048.0 ± 0.3 and 1454.0 ± 0.3 μg/mL, and 460.1 ± 2.7 and 457.4 ± 0.3 μg/mL for both leaf and fruit essential oils, respectively. The results obtained in this study suggest that the leaf and fruit essential oil of Chrysophyllum albidum G. Don could find potential use in the food, cosmetic, and pharmaceutical industries as preservative and pharmaceutical agents.